Olive (Olea Europaea L.): Southern-Italian Biodiversity Assessment and Traceability of Processed Products by Means of Molecular Markers - Alba, V.; Sabetta, W.; Summo, C.; Caponio, F.; Simeone, R.; Blanco, A.; Pasqualone, A.; Montemurro, C. (IntechOpen, 2011)
None